METHODOLOGY FOR ASSESSING THE FINANCIAL STABILITY OF THE TRADE NETWORK - Кравченко, Вікторія (SWorldJournal, 2025)
The article emphasizes that in the current economic situation, assessing the financial condition of enterprises is one of the key tasks for ensuring their stability and effective development. Alternative approaches to assessing the financial condition of